MENO KŪRINIO INTERPRETACIJŲ VERTINIMO PROBLEMA. - Budrytė, Edita (Problems / Problemos, 2012)
This article addresses the question of how we should assess interpretations of artworks. Metacritical theories often disagree on whether requirements of justice and objectivity for interpretations are reasonable. In particular, many problems arise when dealing with opposite, incompatible interpretations of the same artwork. The article reveals two theoretical branches: critical monism and critical pluralism. Monroe Beardsley defends the thesis of "the only correct" interpretation of the artwork, formulating the principles of autonomy and independence while Joseph Margolis offers not to fulfill the criterion of truth, however, to adapt a more relativistic point of view for the assessment of interpretations. This article analyzes the concepts of intentionality and objectivity in relativism given by Margolis as "logic of interpretation".